BRAC/DPHE/UNICEF collaboration on community-based Arsenic response - Jakariya, Md.; Haque, Salma R.; Nickson, Ross T.; Hossain, Md. Zabed; Chowdhury, AMR (BRAC Research and Evaluation Division (RED), 2020)
The severity of the problem of arsenic in ground water in Bangladesh is now well recognized. 97% of the population relics on ground water for drinking and cooking purposes and it is estimated that half of the country may have arsenic in the subsurface. The source of the arsenic is geological and due to the sedimentary processes which lead to accumulation of arsenic and release to groundwater the level found in tubewell water are spatially variable-one well may be highly contaminated whereas nearby another is not The severity of arsenic poising, or arsenicosis, also varies dependent on the length of exposure, the level of arsenic being ingested and the socio-economic (or nutritional) status of the individual concern. BRAC, a non-governmental organisation, in conjunction with DPHE and UNICEF have begun efforts to assess and mitigate the arsenic problem in two thanas of Bangladesh - Sonargaon and Jhikorgacha. Testing has so far been carried out in one union, Boiderbazar union of Sonargaon Thana. 61 % wells of this union were contaminated with arsenic above the Bangladesb standard of 0.05 mgIl. Instantiation and assessment of safe water options has begun. The options being advocated are: treatment of ground water with home based candle filters, treatment of surface water with Pond Sand Filter (PSF), Rain Water Harvesting (RWH). These options are being assessed on several criteria: initial and operating costs; ease of implementation, operation and maintenance; continuity of supply; susceptibility of bacteriological contamination and acceptability to the community. AD of these options have their limitations and none are as easy as obtaining tubewell water directly, however, at present home based filter are proving most popular due to low cost, ease of use and acceptability. Continued manufacturing quality of these home based filter must be ensured and the lifetime of the candle assessed.